Illuminating the future of cohesion through the megatrends of today - Lam, Teng Si (2024)
Building cohesive and resilient communities has become increasingly challenging in today’s climate of rising conflicts and geopolitical tensions. To mitigate the erosion of social cohesion and trust, organisations across all sectors of society must keep abreast of the most influential megatrends and how they are interconnected in impacting social cohesion. By doing so, societies can be better equipped with the foresight to navigate the scenarios and challenges these megatrends may bring.